Quantifying Late Pleistocene to Holocene Erosion Rates in the Hami Basin, China: Insights Into Pleistocene Dust Dynamics of an East Asian Stony Desert. Issue 8 (14th April 2022) - Zhang, Dehai; Wang, Guocan; Abell, Jordan T.; Pullen, Alex; Winckler, Gisela; Schaefer, Joerg M.; Shen, Tianyi
Abstract: Wind is one of the major processes modifying the land surface in the Hami Basin, as evidenced by wind deflation gravel lags, yardangs, and gravel mantled eolian ripples. We report erosion rates for the Hami Basin using cosmogenic 10 Be measurements. Bedrock erosion rates average 0.121 ± 0.0293 mm yr −1, which is similar to those of other wind‐eroded arid basins in East Asia, but is anomalously low when modern near‐surface wind speeds are considered. We posit that interglacial periods experienced lower erosion rates than glacial periods, and that the Hami Basin was likely once a larger dust producer than at present, with Pleistocene dust emissions driven by the eolian deflation of alluvial terrace deposits as well as bedrock weathering and abrasion. Wind erosion and dust production in the Hami Basin was largely regulated by the synoptically controlled spatial‐temporal distribution of precipitation and subsequent landscape evolution since at least the late Pleistocene. Plain Language Summary: The Hami Basin in Xinjiang, China is in the core of the >3 × 10 6  km 2 arid to hyperarid dust generating corridor of the eastern Eurasian continental interior. Quantifying the wind abrasion of bedrock on long timescales, while challenging, is necessary to understand landscape evolution. Based on cosmogenic 10 Be measurements of wind eroded bedrock features (i.e., yardangs) in the Hami Basin, we provide the first quantitative evaluation of bedrock erosion in the stony Hami Basin over the last ∼20 thousand years. Incorporating previous work with our erosion rates, the results indicate that wind erosion rates are lower now than over multiple previous glacial‐interglacial cycles in the Hami Basin. Key Points: Wind erosion rates in the Hami Basin were determined to be ∼0.121 mm yr −1 for the last ∼11–23 ky using cosmogenic 10 Be measurements Interglacial periods likely experienced lower erosion rates than glacial periods due to changes in atmospheric conditions Wind erosion and dust production were regulated by climate and landscape evolution since the late Pleistocene in the Hami Basin